ANALISIS IMPLEMENTASI ERP (ENTERPRISE RESOURCES PLANNING) ORACLE CLOUD FINANCE PADA PT. HADJI KALLA MAKASSAR - Syarifuddin Syarifuddin (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2019)
This study aims to determine the challenges and obstacles in the process of implementing the Oracle Cloud ERP system. Cloud-based ERP models are still rarely used by companies in Indonesia. For Oracle cloud, PT Hadji Kalla was the first group of companies to use in Indonesia. The implementation process lasted for 2 years from 2017-2018. This research is a qualitative approach with analytical methods using phenomenological analysis. Data collection is done by interviewing key informants involved in the system implementation process. The results of this study indicate that the informant feels that sometimes the perception of the user (Buyer) is not the same as the results of the system output after implementation. This causes differences of opinion between the implementor and the user towards the final results of the ERP system implementation. In addition, some outputs that were produced were not in accordance with the applicable financial reporting standards in Indonesia (PSAK). So users need to process again (customize) to suit the needs of users. As well as the user's expectations for the emergence of efficiency, it is precisely for them to feel the impact of additional costs. Because of the increased process and resources needed to support the ERP system. Therefore, for users who will implement, there needs to be an initial process of in-depth introduction between the implementor and the user to equalize. So that disappointment does not arise later on. This research is expected to contribute to the ERP system implementation process in the world of practitioners. While theoretically, the results of this study reinforce the concept of schemata theory in the acceptance of a technology.